Macierzowa reprezentacja ubezpieczenia wielostanowego z niejednorodnym łańcuchem Markowa - Dębicka, Joanna (A Matrix Representation of Multistate Insurance with Non-Homogenous Markov Chain, 2006)
A model for the cash value of a stream of future payments arising from a multistate insurance contract is analyzed. A matrix form for formulas for the first two moments of the cash value of the stream of future payments is derived. The complete theory is illustrated by the analysis of unemployment insurance.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1108, s. 244-268